2019
DOI: 10.1186/s12877-019-1078-2
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a multicentre prospective cohort study to identify predictors of adverse outcome in older medical emergency department patients (the Risk Stratification in the Emergency Department in Acutely Ill Older Patients (RISE UP) study)

Abstract: Background Older patients (≥65 years old) experience high rates of adverse outcomes after an emergency department (ED) visit. Reliable tools to predict adverse outcomes in this population are lacking. This manuscript comprises a study protocol for the Risk Stratification in the Emergency Department in Acutely Ill Older Patients (RISE UP) study that aims to identify predictors of adverse outcome (including triage- and risk stratification scores) and intends to design a feasible prediction model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…We detected no evidence for selection bias but cannot exclude it either. 17 In addition, we only measured biomarker values immediately after arrival at the ED. It is possible that serial biomarker measurement may have yielded different information and a different predictive ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We detected no evidence for selection bias but cannot exclude it either. 17 In addition, we only measured biomarker values immediately after arrival at the ED. It is possible that serial biomarker measurement may have yielded different information and a different predictive ability.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol of this study was published online. 17 This part of the study took place in Zuyderland Medical Centre (MC), a large teaching hospital in the south of the Netherlands, because biomarkers were measured in patients included in this site only. Patients were included if they visited the ED between July 2016 and February 2017, were 65 years old or older, were examined and treated by an internist or gastroenterologist and provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Older ED patients (�65 years) treated by internists or gastroenterologists were eligible for inclusion after informed consent was obtained from the patient or legal representative. The study protocol was approved by the medical ethics committees of Zuyderland MC and MUMC+ (NL55867.096.15) and published online [11]. This study was reported in line with the STROBE (STrengthening the Reporting of OBservational studies in Epidemiology) guidelines [13].…”
Section: Study Design Setting and Study Populationmentioning
confidence: 99%
“…Since many patients feel inhibited to talk about their feelings to the ED staff [8,10], it is likely that their concerns have not been completely exposed in these studies. Recently, we performed the RISE UP study to find predictors of adverse outcomes in older ED patients [11], and found that the severity of concerns in patients and caregivers is predictive of adverse outcomes [12]. It may, therefore, also be possible that specific concerns are predictive of that particular outcome.…”
Section: Introductionmentioning
confidence: 99%